Analisis Tingkat Literasi Digital Mahasiswa dan Dampaknya pada Pembelajaran di Masa Depan - Susanti, Aria Indah; Lestari, Nia Agus (GHANCARAN: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2025)
Higher education institutions, as educational institutions that educate and produce students, need to gain a deep understanding of their digital literacy skills so they can adapt their curriculum and learning strategies to meet current needs. The importance of digital literacy skills is the objective of this study, which aims to examine the impact of digital literacy on future learning. The research approach used is quantitative with descriptive methods. This approach and method were used to obtain an overview of the digital literacy level of Tarbiyah students at UIN Madura. The impact of digital literacy on learning will be discussed using secondary data analysis methods, namely the results of previous research. The population in this study were Tarbiyah students at UIN Madura, and the sampling technique used was simple random sampling, resulting in 48 respondents. The data collection technique used a questionnaire with a digital questionnaire form, namely Google Form. The questionnaire used by the researcher was based on eight components of digital literacy to assess the level of digital literacy of students. The results revealed that the level of digital literacy in all seven dimensions was categorized as high, and one other dimension was categorized as sufficient. The contribution of digital literacy in learning includes improving students’ skills, motivation, and interest in learning, preparing students to be able to face challenges and opportunities in the era of digital technology dominance, developing literacy skills through easy access to information, and improving the ability to learn independently both formally and informally.